Cryptocurrency in the Light of Sentiments : A Bibliometric Approach - Sharma, Diya; Ghosh, Renu; Sharma, Chandra Shekhar (Indian Journal of Finance, 2024)
Purpose : Cryptocurrency has drawn interest from academia and business, particularly amid notable spikes in the price of Bitcoin. The presence of cryptocurrencies and their technology-focused investments are intimately related to investor behavior. Due to its unpredictability, mood has a greater impact on Bitcoin investing than technical factors. The purpose of this study was to perform a bibliometric review in this field. Methodology : Using VOSviewer software, this article attempted to do a bibliometric study of papers on sentiments and cryptocurrencies included in the Scopus database. The study complied with the PRISMA framework, which is the recommended practice for systematic reviews. Findings : The findings showed that this field is seeing a massive increase in research activity. A total of 483 distinct authors wrote 151 articles. Studies that examined changes in the Bitcoin industry have received the attention they deserve in finance publications. Three connected clusters were discovered by co-citation analysis, indicating that studies are looking at how cryptocurrencies work as financial market investments using social media sentiments. Practical Implications : The study on cryptocurrency sentiments offered valuable insights for investors, policymakers, and the market. It informed decision-making on investments, risk management, and regulations, providing a foundation for practical tools in the dynamic cryptocurrency market. These insights will contribute to a resilient and sustainable ecosystem, guiding public awareness for responsible cryptocurrency use. Originality : To the best of our knowledge, this work is the first in this developing field to do a bibliometric literature evaluation on Scopus articles.